Article RETRACTED due to manipulation by the authors The Hybrid Learning System With Project Based Learning: Can It Increase Creative Thinking Skill and Learning Motivation in Physical Education Learning? - Rifqi Festiawan; Eko Sumanto; Ayu Rizky Febriani; Asep Angga Permadi; Z. Arifin; Andri Wahyu Utomo; Wildan Alfia Nugroho; Kukuh Wahyudin Pratama (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to determine the effect of hybrid learning using the project based learning method on creative thinking abilities and learning motivation. The research method is the true experimental research technique, utilizing The Randomized Pretest-Posttest Control Group Design. The population for this study included all students in Senior High School 1 Purwokerto, totaling 1015 students across 36 classes. Simple random sampling was employed to select a total sample of 112 students (n = 112, age = 17.1 ± 1.2 years). This research uses two instruments to obtain data, including 1) The Torrance Tests of Creative Thinking (TTCT) and 2) The Motivated Strategies for Learning Questionnaire (MSLQ). The data analysis used was the data normality test, data homogeneity test, paired t-test and independent t-test. The data used is normally distributed (sig=0.434) and homogeneous (sig=0.533), The research results show that the effect of Hybrid Learning with the Project Based Learning method on creative thinking skills and learning motivation (sig=0.000), control group (sig=0.002), and there is a significant difference in effect between the treatment group and the control group (sig=0.000). It can be concluded that 1) PjBL model has a favorable impact on students' critical thinking skills in physical education, 2) PjBL model positively influences learning motivation in physical education, and 3) PjBL model yields a more positive outcome compared to the direct teaching model in enhancing students' creative thinking skills in the context of physical education.